Inhibition of human neutrophil locomotion by the polyamine oxidase-polyamine system. - Ferrante, A (1985)
The polyamines, spermine and spermidine, in the presence of either bovine serum [containing polyamine oxidase (PAO) activity] or partially purified PAO, inhibited human neutrophil locomotion. This effect could not be produced by either bovine serum, PAO, or the polyamines alone. The results suggested that at least two of the products generated during the oxidation of polyamines by PAO, namely H2O2 and ammonia, are not responsible for the effects on neutrophils. Acrolein, a breakdown product of other products (aminoaldehydes), was found to inhibit the neutrophil functions. Since polyamines, and possibly PAOs, accumulate at inflammatory sites, products of the PAO-polyamine reaction could function as regulators of the inflammatory response.